(untitled) (ENTHYMEMA, 2016)
This article argues for the pedagogical usefulness of engaging with literary texts in the formal training of physicians and healthcare workers. It suggests that particular “skills” in reading and engaging with narrative are as readily teachable to healthcare students as are skills in reading x-rays or in diagnosing symptoms. It focuses on three phenomena associated with literary (and other forms) of narrative – namely, the recognition of characters, vicarious experience, and the experience of fellow feeling – and relates them to three categories in cognitive psychology: Theory of Mind, Narrative Transportation, and Empathy. It presents a survey of empirical studies in cognitive psychology that demonstrates the effectiveness of literary narrative in producing these psychological states, and ends by demonstrating how the teaching of a literary narrative – Bastard Out of Carolina – has enhanced these states in students planning on a career in medicine. Such enhancement, the article suggests, are produced by literary features such as imagery, defamiliarization, and patterned organization on the levels of phonology, semantics, and story structure.